Isolation, Detection, and Estimation of Various Amylase Producing Bacteria in Various Soil Samples - Mir, M. A.; Ashraf, Mohammad Waqar; Hussain, Altaf; Mir, Bilal Ahmad (Current Organocatalysis, 2022)
Background: Soil is an ultimate source of all types of nutrients, which have both biological and non-biological importance. Studies are being carried out to isolate the various type of micro- organism from soil which has much more importance. So in the present study, amylase-producing bacteria have been isolated from various soil samples. Aim: The isolation, identification, and estimation of various microbial strains for α-amylase enzyme production and then the inhibition of the growth of these microbial stains. Methods: The bacterial strains were isolated and then identified by various microbiological methods, including Gram’s staining method followed by several biochemical methods such as litmus test, Gelatin test and Urea agar media, and by viable cells. Results: Altogether, three microbial strains were identified from the soil samples in the concerned study. The concerned strains include- Shigella, Proteus and Bacillus, respectively. The concerned microbial strains were then analyzed for the amount of amylase enzyme, and it had been found that Bacillus sp produce much more amount of amylase followed by Shigella sp, and lesser amylase enzyme- producing activity was found in Proteus sp. The isolated bacteria were then analysed for inhibition of their growth by water and ethanolic extracts of Cuminum cyminuni. Among the extracts, it had been found that water extracts exhibited more inhibiting capacity than ethanolic extracts. The study also revealed that among the bacterial strains, the Shigella sp got much more affected by the concerned plant extracts followed by Proteus sp and the least inhibition was observed against the Bacillus sp. Conclusion: As per the above study, it is being concluded that - three amylase-producing bacteria viz Shigella, proteus, bacillus sp were isolated from the soil samples. These isolated microbial strains could be used for the decomposition of cholesterol levels in humans in addition to other microbial activity. These isolated bacterial could sometimes be averse, so their growth could be stopped by various biological and chemical substances like Gentamicin and by various Plant extracts viz, Cuminum cyminuni Plant.
Keywords: proteus